PENGARUH PEMBIASAAN MEMBACA AL QUR’AN TERHADAP PENINGKATAN MENGHAFAL AL-QUR’AN - Laila, Hidayatul; Basri, Hasan (Fakultas Agama Islam Universitas Muhammadiyah Luwuk, 2024)
In this article will discuss the habituation of reading the Qur'an on the improvement of memorising the Qur'an. Where this study aims to determine whether there is an effect of habituation of reading the Qur'an on improving memorisation of the Qur'an in students at SMA Muhammadiyah 8 Cerme. This research uses a quantitative approach. The data collection techniques used in this study are: questionnaire and documentation. This is evidenced from the results of the Hypothesis Test obtained results with Thitung (6,408) > Ttabel (953) and sig probability value (0.000) < (0.05). From these results it can be concluded that there is an influence of reading the Qur'an on the improvement of memorising the Qur'an in Al-Qur'an class students of SMA Muhammadiyah 8 Cerme. The influence between the two variables is also evidenced by the correlation coefficient value which shows (0.801) or 80%, this is included in the strong relationship category. The effect of the habit of reading on improving the ability to memorise the Qur'an is 62% and the remaining 38% is the influence of other variables that are not used as variables in this study.